Green skill investment and green job productivity: the critical mediation of digital readiness - Fadilah, Desti Alya; Hidayat, Agi Syarif (Manajemen dan Bisnis, 2026)
The transition toward a sustainable and green aconomy has increased the demand for green jobs that are supported by skilled and digitally ready human resources. In Indonesia, particulary in semi-urban areas such as Cirebon City, challenges related to environmental pressures, limited digital adoption, and workforce capability gaps remain significant. This study aims to examine the effect of green skill investment on green job labor productivity, with digital technology adoption readiness serving as a mediating variable. A quantitative survey approach was employed, collecting primary data from workers engaged in green job sectors, including environmental agencies, the departement of manpower, and waste management units in Cirebon City. Data were analyzed using a structural modelling approach to explore direct and mediated relationships among variables. The finding indicate that investment in green skills enchances labor productivity and strengthens workers’ readiness to adopt digital teknology. Digital Technology adoption readiness also plays an important role in translating green skills into productive work outcomes, highlighting the interconnected nature of green competencies and digital transformation. These results suggest that policies and training programs aimed at developing green jobs should integrate environmental skill development with digital readiness to support sustainable and inclusive workforce transformation.